TREATMENT APPROACH FOR JUVENILE IDIOPATHIC ARTHRITIS-RELATED UVEITIS: 2012 UPDATE - Francesco Zulian; C. Birolo; M. E. Zannin ("Paediatrician" Publishers LLC, 2012)
Chronic anterior uveitis is the most common extra-articular complication of juvenile idiopathic arthritis. It is more frequent in the early onset forms with a higher prevalence in the oligoarticular (40%) than in other juvenile idiopathic arthritis subtypes (5-14%). The risk for severe visual impairment is still high due to the development of sight-threatening complications (synechiae, band keratopathy, cataract, glaucoma, cystoid macular oedema. Treatment is not standardized and requires a complex decision-making process, involving a close collaboration between paediatric ophthalmologist and rheumatologist. Topical therapy alone is often inadequate to control ocular inflammation and bulbar injections are too invasive to perform in children therefore immunosuppressive treatment is often advocated. Low dose methotrexate is the second-line agent mostly used although no controlled studies comparing effects of early to late methotrexate treatment have been reported. Mycophenolate mofetil is effective in controlling inflammation in methotrexate -refractory patients. Its efficacy, however, seems to be more relevant in intermediate or posterior uveitis, than in juvenile idiopathic arthritis uveitis and scleritis. Anti-TNFα agents, namely infliximab and adalimimab showed effectiveness in open-label studies but no wide controlled trials have been reported so far. Adalimimab is as effective as infliximab but has an easier way of administration and a better drug tolerance. Abatacept should be used in anti-TNF refractory patients with juvenile idiopathic arthritis uveitis.